Flocculating performances of exopolysaccharides produced by a halophilic bacterial strain cultivated on agro-industrial waste - TOKSOY ÖNER, EBRU; ŞAM, SERDAR (ELSEVIER SCI LTD, 2011)
This study reports the first systematic investigation of the flocculation dynamics of exopolysaccharides (EPSs) produced by a halophilic bacterial strain grown on pretreated molasses as fermentation substrate. The potential use of these EPSs as an easily biodegradable, natural alternative for synthetic polyelectrolytes which are widely used and contain toxic and carcinogenic monomers was investigated. Flocculating activities of the EPS samples in synthetic water, synthetic sea water and natural sea water media which were used as model raw waters were monitored via the Photometric Dispersion Analyser (PDA 2000) instrument and removals were determined by measuring residual turbidities. One of the six EPS specimens, which formed the largest flocs thus performed highest turbidity removal, exhibited flocculation performance and particle removal efficiency comparable with commercial cationic, nonionic and anionic synthetic polyelectrolytes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Bioflocculant; Exopolysaccharide; Extremophile; Flocculation; Halomonas; BIOLOGICAL TREATMENT; BIOPOLYMER FLOCCULANT; BIOFLOCCULANT; WATER; BEHAVIOR; SURFACE